2019
DOI: 10.1088/1748-3190/ab295b
|View full text |Cite
|
Sign up to set email alerts
|

Effective locomotion at multiple stride frequencies using proprioceptive feedback on a legged microrobot

Abstract: Limitations in actuation, sensing, and computation have forced small legged robots to rely on carefully tuned, mechanically mediated leg trajectories for effective locomotion. Recent advances in manufacturing, however, have enabled the development of small legged robots capable of operation at multiple stride frequencies using multi-degree-of-freedom leg trajectories. Proprioceptive sensing and control is key to extending the capabilities of these robots to a broad range of operating conditions. In this work, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 113 publications
5
17
0
Order By: Relevance
“…Wood and co‐workers commonly utilize bimorph piezoelectric elements to realize complex motion, including flight (linear, bending, rotary) 120. Demonstrations include climbing microrobots (Figure 6e),121 microaerial vehicles, high speed microrobots such as the Harvard Ambulatory MicroRobot (HAMR‐VP) (Figure 6f),122 insect robots123 such as the centipede‐inspired robot in Figure 6g,124 proprioceptive, high speed quadrupedal robots (Figure 6h),125 and mini resonant ambulatory robots 106,118,126,127. The piezoelectric actuators in the HAMR, the centipede, and the RoboBee (Figure 6i–k) are composite laminates of two piezoelectric ceramic layers (PZT‐5H) with nickel electrodes bonded to a central conductive carbon fiber layer tipped with aluminum 5,123.…”
Section: Piezoelectric Ceramics Polymers and Compositesmentioning
confidence: 99%
“…Wood and co‐workers commonly utilize bimorph piezoelectric elements to realize complex motion, including flight (linear, bending, rotary) 120. Demonstrations include climbing microrobots (Figure 6e),121 microaerial vehicles, high speed microrobots such as the Harvard Ambulatory MicroRobot (HAMR‐VP) (Figure 6f),122 insect robots123 such as the centipede‐inspired robot in Figure 6g,124 proprioceptive, high speed quadrupedal robots (Figure 6h),125 and mini resonant ambulatory robots 106,118,126,127. The piezoelectric actuators in the HAMR, the centipede, and the RoboBee (Figure 6i–k) are composite laminates of two piezoelectric ceramic layers (PZT‐5H) with nickel electrodes bonded to a central conductive carbon fiber layer tipped with aluminum 5,123.…”
Section: Piezoelectric Ceramics Polymers and Compositesmentioning
confidence: 99%
“…1) Vertical Leg Stiffness: Template dynamics resulting from bioinspired locomotion models [20] such as Single Leg Inverted Pendulum (SLIP, [21]) and Lateral Leg Spring (LLS, [22]) have informed the design of robotic systems including HAMR. Specifically, recent studies [10] on HAMR have demonstrated the importance of vertical leg stiffness to robot locomotion performance as a function of locomotion frequency.…”
Section: Transmission Dynamicsmentioning
confidence: 99%
“…As a first step towards predicting the sagittal plane dynamics resulting from scaling down, we experimentally determined the stiffness of the lift transmission using the procedure described in Doshi et al, [10]. Using the experimental setup depicted in Figure 3a, we measured vertical stiffness as a function of leg height for each of the four lift transmissions and found that it ranged from 34.52 to 72.11 Nm −1 (Figure 3b).…”
Section: Transmission Dynamicsmentioning
confidence: 99%
See 2 more Smart Citations